SYNTHESIS AND CRYSTAL STRUCTURE OF THE COMPLEX COMPOUND OF Cu(II) ION, SALICILAMIDE AND TRIETHANOLAMINE (Scientific journal of the Fergana State University, 2024)
The article discusses the synthesis of the complex [Cu(L1)2(TEA)]·2H2O (Sal-salicylamide, TEA-triethanolamine) and its crystal structure. At the same time, the dependence of the reaction yield on time, temperature and concentration of reagents was also studied. The synthesized complex compound was studied by Fourier transform infrared spectroscopy, UV spectroscopy, elemental analysis and X-ray diffraction. A. Rao., D. Sribalan., G. Sandhya., K. Nonoyama., H. Ojima., M. Nonayama and their teams. In contrast to the work of these scientists, for the first time (with mixed ligands) a complex compound of salicylamide and triethanolamines of the composition [Cu(L1)2(TEA)]·2H2O was synthesized in a solution with copper; single crystals were grown and X-ray diffraction analysis was carried out at the Institute of Bioorganic Chemistry of the Academy of Sciences RUz on the XtaLAB Synergy diffractometer (Rigaki, Japan), installed in a public access center.